Respiratory incidents in response to air quality deterioration in the summer and early autumn season - Ewa Niewiadomska; Małgorzata Kowalska; Aleksandra Micek; Elwira Zajusz-Zubek (PLoS ONE, 2025)
The paper presents the results of an ecological study completed within the warm seasonal period of 01/07/2024–31/10/2024. The aim is to assess the relationship between ambient air quality deterioration and acute respiratory incidents occurring in the inhabitants of Gliwice (Poland; Upper Silesian agglomeration). The number of daily medical services (MS) due to respiratory diseases and illnesses was obtained from the register of the National Health Fund (Silesian Voivodeship Branch in Katowice). The daily mean values of aerosanitary factors in Gliwice came from the mobile air pollution laboratory of the Silesian University of Technology in Poland. The relative risk ( RR ) of MS was estimated using a Poisson log-linear model considering independent environmental factors (meteorological factors and air pollutant concentrations) or confounding factors (astronomical season and day of the week). The highest number of MS due to respiratory diseases refers to acute nasopharyngitis and asthma exacerbation, mostly in children aged 0–9 years. A significant impact was observed in the case of particulate matter concentration increase and number of MS due to acute nasopharyngitis, laryngitis and tracheitis, pneumonia, asthma exacerbation, in the case of nitrogen oxides appropriately acute nasopharyngitis, bronchitis and/or bronchiolitis, pneumonia, asthma exacerbation. Additionally, a longer time of exposure was associated with a higher risk of MS due to respiratory incidents. The increase in wind speed and relative humidity was significantly associated with a higher number of bronchitis and asthma exacerbation while a higher temperature and higher 8-hour ozone concentration remain protective of both MS. The results are essential for effectively communicating environmental health risks, educating the public about potential threats, and pressuring legislators responsible for legislation and risk management.